2013
DOI: 10.4238/2013.march.26.2
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of rs1799983 (G>T) and rs1800780 (A>G) of the eNOS gene associated with susceptibility to essential hypertension in the Chinese Hui ethnic population

Abstract: ABSTRACT.We investigated a possible association of polymorphism of the eNOS gene and essential hypertension in the Chinese Hui population; polymorphisms of rs2070744 (T>C), rs1799983 (G>T), rs1800780 (A>G), and rs3918181 (A>G) loci of the eNOS gene were examined. We found that the genotypic frequencies at rs1799983 and rs1800780 loci differed significantly between patients with essential hypertension and control cohorts. The allelic frequency of the rs1799983 locus also differed significantly between essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Our results also suggest that hypertensive subjects bearing mutant genotypes ( Glu/Asp and Asp/Asp ) have higher BP than those with wild genotype ( Glu/Glu ) in Chinese male hypertensive subjects. This result is consistent with previous studies 16,17 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results also suggest that hypertensive subjects bearing mutant genotypes ( Glu/Asp and Asp/Asp ) have higher BP than those with wild genotype ( Glu/Glu ) in Chinese male hypertensive subjects. This result is consistent with previous studies 16,17 .…”
Section: Discussionsupporting
confidence: 94%
“…The human eNOS gene is located at 7q35-36 and spans 21 kb with 26 exons and 25 introns 15 , and has been shown to be polymorphic. It is reported that the Glu298/Asp (G894→T conversion at nucleotide position 894) polymorphism of the eNOS gene decreases NO production and subsequently influences the development of EH and atherosclerosis 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, several studies have examined whether NOS3 polymorphisms are associated with hypertension. Increased risk of hypertension associated with the variant alleles for the g.-786T>C, g.-665C>T, 4b/4a VNTR and Glu298Asp polymorphisms have been observed in some studies (Uwabo et al, 1998; Jachymova et al, 2001; Hyndman et al, 2002; Pereira et al, 2007; Nejatizadeh et al, 2008; Niu and Qi, 2011; Salvi et al, 2013; Yang et al, 2013; Levinsson et al, 2014; de Miranda et al, 2015; Liu et al, 2015). However, lack of association of these polymorphisms with hypertension was reported in many other studies (Miyamoto et al, 1998; Kato et al, 1999; Benjafield and Morris, 2000; Schneider et al, 2000; Tsujita et al, 2001; Sandrim et al, 2006a; Sandrim et al, 2006c; Pereira et al, 2007; Conen et al, 2008).…”
Section: Genetic Polymorphisms In the Nos3 Genementioning
confidence: 97%
“…It has been shown that VEGF inhibition induces a decrease in eNOS expression and thus in NO production [ 21 ], and that this phenomenon is linked to the induction of hypertension, one of the most common dose-limiting toxicities of VEGF inhibitors [ 22 ]. Previous studies have demonstrated an association between specific eNOS polymorphisms and hypertension [ 14 , 23 ]. A positive correlation between the induction of hypertension and the clinical benefit of bevacizumab has also been observed [ 13 ].…”
Section: Discussionmentioning
confidence: 99%